Pengaruh Keterlambatan Penerbangan Terhadap Kepuasan Penumpang pada Maskapai Super Air Jet di Bandar Udara Internasional Sultan Aji Muhammad Sulaiman Sepinggan Balikpapan - Ni Kadek Ratna Dewi; Andi Syaputra (Jurnal Transformasi Bisnis Digital, 2025)
Air transportation is a mode of transportation that continues to grow rapidly in Indonesia, marked by the construction of new airports and the improvement of facilities at existing airports. However, flight delays remain one of the main issues faced by the aviation industry, including by Super Air Jet. This study aims to analyze the effect of flight delays on passenger satisfaction at Super Air Jet at Sultan Aji Muhammad Sulaiman Sepinggan International Airport, Balikpapan. The study used a quantitative approach involving 97 respondents who were Super Air Jet passengers. Data management was carried out through several stages of testing, namely instrument testing (validity and reliability), data quality testing (linearity, normality, and heteroscedasticity), and hypothesis testing using simple linear regression analysis, t-test, and coefficient of determination (R²) with the help of IBM SPSS Statistic 22 software. The results of the study indicate that flight duration has a significant effect on passenger satisfaction. This finding emphasizes the importance of improving service quality, especially in efforts to minimize delays, in order to maintain passenger trust in the airline. This study is expected to be a reference for Super Air Jet management in identifying the main causes of flight delays and developing effective strategies to improve passenger satisfaction.